Single‐Site and Cooperative Bond Activation Reactions with Ylide‐Functionalized Tetrylenes: A Computational Study. Issue 47 (26th October 2021) - Steinert, Henning; Löffler, Julian; Gessner, Viktoria H.
Abstract: Due to their transition metal‐like behavior divalent group 14 compounds bear huge potential for their application in bond activation reactions and catalysis. Here we report on detailed computational studies on the use of ylide‐substituted tetrylenes in the activation of dihydrogen and phenol. A series of acyclic and cyclic ylidyltetrylenes featuring various α‐substituents with different σ ‐ and π ‐donating capabilities have been investigated which demonstrate that particularly π ‐accepting boryl groups lead to beneficial properties and low barriers for single‐site activation reactions, above all in the case of silylenes. In contrast, for the thermodynamically more stable germylenes and stannylenes an alternative mechanism involving the active participation of the ylide ligand in the E−H bond (E=H or PhO) activation process by addition across the element carbon linkage was found to be energetically favored. Furthermore, the boryl substituted tetrylenes allowed for a further activation pathway involving the active participation of the boron element bond. These cooperative mechanisms are especially attractive for the heavier cyclic ylidyltetrylenes in which the loss of the protonated ylide group is prevented due to the cyclic framework. Overall, the present studies suggest that cyclic ylide‐substituted germylenes and stannylenes bear huge potential for cooperative bond activations at mild conditions which should be experimentally addressed in the future. Abstract : Computational studies on the use of ylide‐functionalized heavier carbenes (with E=Si, Ge, Sn) in bond activation reactions revealed that these species can undergo both, single‐site as well as cooperative activation processes. The latter involve the active participation of the ylide moiety and are particularly attractive for the more stable germylenes and stannylenes, thus opening new perspectives for future catalyst design.